Statewide assessment of air quality changes in Florida during the COVID-19 pandemic - Mohammad Shareef Ghanim; Deepti Muley; Peiman Kianmehr; Mohamed Kharbeche (Results in Engineering, 2023)
The COVID-19 pandemic has forced many countries from all over the world to adopt extreme measures to suppress the spread of the pandemic. These measures have triggered changes in air quality. Many studies showed an overall short-term improvement in air quality. This study investigates the long and short-term impacts of COVID-19 pandemic on air quality in the State of Florida. Three air quality indicators (AQI) from 69 stations located in 30 counties in the State of Florida were analyzed for 2015–2021. These pollutants are Fine Particulate Matters (PM2.5), Nitrogen Dioxide (NO2), and Sulfur Dioxide (SO2). The long-term changes in pollutant levels were assessed via Time-Lag linear regression analysis (TLR). The results show that PM2.5 levels dropped from 8.88 to 8.24 μg/m3 between 2015 and 2021. However, the ANCOVA test shows that the TLR's slope for PM2.5 is insignificant, with a p-value of 0.859. Thus, there was no statistical evidence that the changes in 2020 and 2021 differ from previous years. NO2 levels fluctuated over the study period between 13.0 and 16.0 ppm with no identified trend. Nonetheless, the regression slope was also insignificant, with a significance of 0.401. The average SO2 concentrations steadily dropped from 4.3 ppb in 2015 to 2.0 ppb in 2020 and 2.62 ppb in 2021, with a regression slope significance of 0.001. It is concluded that pollutants' levels behave differently during the lockdown and release periods, indicating that the lockdown contribution to reduce industrial activities is reflected on air quality rather than mobile source emissions.